Color stability and surface roughness of chitosan- and nanodiamond-modified bisacrylic resin - Victoria Tamara Perchyonok; John Souza; Marcela Fernanda Küll; Thaís Yumi Umeda Suzuki; Ana Teresa Maluly-Proni; Paulo Henrique dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: The aim of this study is to evaluate the effect of chitosan or nanodiamond incorporation on the color stability and surface roughness of a bisacrylic resin subjected to artificial aging. Four bisacrylic resins were evaluated, namely, control, chitosan-modified material, nanodiamond-modified material, and chitosan-nanodiamond-modified material. Twenty-four specimens were prepared for each material. The surface roughness was determined using a profilometer with a cut-off of 0.25 mm. The baseline color was measured according to the CIE L*a*b* system using a reflectance spectrophotometer. After these tests, the specimens were individually immersed in cola soft drink, red wine, or distilled water (n = 8) for 28 days. After the aging, the surface roughness and final color were re-evaluated. The color stability was determined using the difference between the coordinates obtained before and after the aging process. The data on roughness and color change were evaluated using ANOVA and the Tukey test (α = 0.05). The results show that the incorporation of nanodiamonds and chitosan into a bisacrylic resin provided a better color stability to the materials (p = 0.007). The storage in red wine resulted in a higher variation in the surface roughness values, especially when only the nanodiamond was incorporated to the material (p < 0.05). The incorporation of both chitosan and nanodiamonds are promising in providing an improvement in the properties of the bisacrylic resin when they are simultaneously incorporated in the product.